Detection of some secondary metabolites of Beauveria bassiana and the potential effects on Spodoptera littoralis - Wessam Houssiny Bakr; Mohemed Farouk Ghaly; Wafaa Ghatwary Tantawy; Samah Nour El-Shafeiy (Chemical and Biological Technologies in Agriculture)
Abstract Background Beauveria bassiana is one of the most renowned entomopathogenic fungi and has recently been recognized as a potential biopesticide for a wide range of insect pests. The secondary metabolites of B. bassiana are believed to contribute to its pesticidal activity. Meanwhile, the Egyptian cotton leafworm, Spodoptera littoralis, is a significant pest that causes considerable damage to various key crops. Results In this study, secondary metabolites were extracted using ethyl acetate from both the culture medium filtrate and the mycelia separately. Subsequently, the extracts were separated via thin-layer chromatography into six fractions from the medium filtrate (F0:F5) and ten fractions from the mycelia (M1:M10). All fractions were assessed for their insecticidal effects on second instar larvae of S. littoralis. The treatment of F0 resulted in the highest larval mortality rate of 61.11%, followed by M3 with a mortality rate of 45.19%. M2 and M8 had similar effects, each resulting in a mortality rate of 40.00%. Furthermore, scanning electron microscopy revealed cuticle disorders and deformations in larvae treated with all treatments. Fractions exhibited the highest mortality rates in S. littoralis larvae, and the total injuries were analyzed using GC/MS, which revealed the presence of eight bioactive compounds. Notably, this study represents the first detection of 2,4-di-tert-butylphenol in the mycelia of B. bassiana, a compound known for its high toxicity. In addition, other compounds contributed to the observed experimental results. Conclusion These findings indicate that B. bassiana could serve as a sustainable source of bioactive metabolites with significant insecticidal effects on S. littoralis. This suggests a strong potential for improving integrated pest management (IPM), particularly when large-scale production is implemented. Graphical abstract